Designing learning experiences on climate change for undergraduate students of different majors - Carrillo-Nieves, Danay; Clarke-Crespo, Emilio; Cervantes-Avilés, Pabel; Cuevas-Cancino, María; Vanoye-García, Ana Y. (Frontiers in Education, 2024)
Education about climate change faces an evolution of the knowledge, and universities should respond with innovative learning processes. As facilitators can adapt to these changes, they will be able to improve learning experiences for students. In this work, learning experiences about climate change were evaluated in undergraduate students without engineering background, as function of the size of the group, duration of the course, gamification activities and technology and virtual tools experiences. The implementation of these activities in the intensive 5-week course focused on climate change education has revealed valuable insights into student motivation, attitude, knowledge acquisition, and engagement. Notably, students’ trust in information sources about climate change exhibited variations, with global organizations garnering higher confidence compared to local and personal sources. In a 15-week course exposed to virtual tools (e.g. escape room), the diagnostic test highlighted a 53% understanding level, particularly challenging in numeric aspects. However, the escape room significantly improved results in the final exam, demonstrating a 93% correctness rate, emphasizing the effectiveness of the activities in reinforcing key climate change concepts. On the other hand, the emergence of climate change-themed escape room as an engagement tool demonstrated its potential in enhancing knowledge acquisition and cooperative learning. In addition, Escape room offered an immersive environment that encourages active participation, enabling students to grasp complex climate concepts and solutions more effectively. The study underscores that climate education should go beyond facts, emphasizing universities’ crucial role in nurturing the “climate change generation” with the knowledge and motivation for meaningful contributions to climate action and policy formulation.